Paternal calorie restriction prior to conception alters anxiety-like behavior of the adult rat progeny. (February 2016) - Govic, Antonina; Penman, Jim; Tammer, Amanda H.; Paolini, Antonio G.
Highlights: Paternal influences on adult offspring anxiety-like behavior was examined. Paternal calorie restriction (CR) decreased the anxiety behavior of the progeny. Food intake, body weight and leptin levels was reduced in the offspring of CR males. Paternal corticosterone treatment failed to alter offspring behavior. CR offspring exhibit a profile adapted to an environment of limited food supply. Abstract: The maternal environment influences a broad range of phenotypic outcomes for offspring, with anxiety-like behavior being particularly susceptible to maternal environmental perturbations. Much less is known regarding paternal environmental influences. To investigate this, adult male rats were exposed to 25% calorie restriction (CR) or glucocorticoid elevation (CORT; 200 μg/ml of corticosterone in drinking water) for ∼6 weeks prior to breeding. Elevated plus maze (EPM), open field (OF), predator odor (cat urine), and acoustic startle/pre-pulse inhibition (AS/PPI) were characterised in the adult male offspring. Plasma concentrations of corticotrophin-releasing hormone (CRF), adrenocorticotropin hormone (ACTH), and serum lepin were characterised in both sires and offspring. Maternal care received by litters was additionally observed. Expectedly, CR and CORT treatment attenuated weight gain, whilst only CR induced anxiolytic behavior in the EPM. The adult offspring sired by CR males also demonstrated a reduction in weight gain, food intake and serum leptin levels when compared to controls. Moreover, CR offspring demonstrated an anxiolytic-like profile in the EPM and OF, enhanced habituation to the AS pulse, reduced PPI, but no alteration to predator odor induced defensiveness compared to control. CORT offspring failed to demonstrate any behavioral differences from controls, however, exhibited a trend towards reduced ACTH and leptin concentration. Collectively, the results indicate that a reduction in calories in males prior to conception can affect the behavior of adult offspring. The phenotypic transmission of CR experiences from fathers to the progeny could potentially be mediated epigenetically. The role of glucocorticoid elevation and maternal care are also discussed.